Prenatally Diagnosed Isolated Coronary Arterial Fistula Leading to Severe Complications at Birth. (26th March 2018) - Wacker-Gussmann, A.; Esser, T.; Lobmaier, S. M.; Vogt, M. O.; Ostermayer, E.; Oberhoffer, R.
Abstract : Prenatal diagnosis of a huge coronary artery fistula between the left coronary artery and the right ventricle was made by Doppler echocardiography at 22 weeks of gestation. Progression of the dilated fistula was monitored throughout pregnancy. The size of the fistula increased enormously up to 11 mm. Death occurred at birth. Monitoring of these fetuses is essential as severe complications can occur during pregnancy or at birth.